PENANGANAN PENYELUNDUPAN ROKOK ILEGAL DI INDONESIA STUDI TENTANG (PEREDARAN ROKOK DI INHIL), RIAU - Nova Trikanti; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research aims to find out how the Efforts to Handle Illegal Cigarette Smuggling in Indonesia Study on (Illegal Cigarette Circulation in Inhil), Riau in 2018-2021 which is motivated by the illegal trade of cigarettes from abroad entering Indonesia. In Indonesia, it is the second country with the largest cigarette market share in the world and the third country with the number of cigarette consumers after China and India. Indonesia's tobacco tax is an important one in national income. 2017-2018 with tax revenue of Rp. 302.9 trillion. The city of Tembilahan Inhil is a liaison between Indonesia and neighboring countries which creates opportunities for smuggling of illegal cigarettes from abroad. Bea cukai as a government official who is responsible for the flow of export and import traffic tries to break the circulation of illegally imported cigarettes from abroad. This study uses a qualitative method. The data collected uses data from library research, books, journals, articles and websites. This study uses the perspective of pluralism, the concept of Non-Traditional Security, the theory of international trade and the level of nation-state analysis Illegal cigarettes from abroad come from Vietnam and Singapore. Bea cukai Perform various efforts, namely: 1). Demolition supervision, 2). Sea patrol, 3). Market operations, 4). Socialization of illegal cigarettes, 5). Based on RI Law no. 39 of 2007. With various efforts made, it is still not optimal because there are still many circulation of illegal cigarettes that are sold in the market, such as shops and stalls which are not small in number which can be detrimental to the domestic cigarette industry, detrimental to excise and state taxes. Keywords: cigarette excise, import, smuggling, illegal cigarettes.